Association of preoperative cerebral oxygenation with concurrent neurobehavioral scores in term neonates with congenital heart disease compared to healthy controls - Tran, Nhu N.; Miner, Anna; Adeleke, Eniola; Phan, Rene; Brady, Ken M.; Brecht, Mary-Lynn; Friedlich, Philippe; Zhou, Geena; Rajagopalan, Vidya; Peterson, Bradley S.; Votava-Smith, Jodie K. (Frontiers in Pediatrics, 2025)
Objective1st: To determine the association of cerebral oxygenation (rcSO2) and concurrent neurodevelopmental outcomes between neonates with congenital heart disease (CHD) and healthy controls. 2nd: To examine the association of cerebral fractional tissue oxygen extraction (FTOE) with concurrent neurodevelopmental outcomes in the two groups. 3rd: To evaluate how type and severity of CHD influenced the associations in our primary and secondary objectives.Study designOur secondary analysis included 137 neonates (74 with CHD and 63 healthy controls). We used linear regression models to examine the association of the predictors (i.e., cerebral oxygenation, FTOE, type and severity of CHD) with the percentage of abnormal neurobehavioral scores (outcome). The models included the main effects of group, rcSO2, and a rcSO2-by-group interaction (examined differences between groups) with covariates of postconceptional age at exam, sex, ethnicity, and preductal peripheral oxygen saturation on the percentage of abnormal neurobehavioral scores. We also performed separate regression models separately in each group. We used these models for the 2nd and 3rd objectives, replacing rcSO2 with FTOE and type and severity of CHD as predictors.ResultsNeonates with CHD had lower rcSO2 values (67% vs. 79%; p < 0.001) and higher FTOE values (0.27 vs. 0.19; p < 0.001) compared to healthy controls. The association of rcSO2 with the neurobehavioral scores significantly differed between groups (p = 0.004). In the CHD group, increased rcSO2 showed a trend toward better neurodevelopmental outcomes. However, increased rcSO2 associated significantly with poorer neurodevelopmental outcomes in the healthy group. Additionally, FTOE significantly differed between groups (p = 0.012). The CHD group showed a trend towards increased FTOE and poorer neurodevelopmental outcomes. Conversely, increased FTOE associated significantly with better neurodevelopmental outcomes in the healthy group.ConclusionsThe CHD and healthy neonates had significantly different associations of both rcSO2 and FTOE with the neurobehavioral scores. Our findings suggest that both increased and decreased rcSO2 and FTOE may negatively affect concurrent neurodevelopmental outcomes in neonates. Our findings also imply a critical range of rcSO2 values, where extreme oxygenation on either side may be harmful. Neonates with CHD and healthy controls may exhibit different neurodevelopmental responses to increased rcSO2 and FTOE due to differing metabolic demands.